Impact of an early weighing policy on neonatal hypernatraemic dehydration and breast feeding. Issue 4 (2nd May 2007) - Iyer, N P; Srinivasan, R; Evans, K; Ward, L; Cheung, W-Y; Matthes, J W A
Abstract : Aims: To ascertain the effect of a policy of early weighing on the detection and severity of neonatal hypernatraemic dehydration (NHD) and on breastfeeding rates in the short and medium term. Methods: A policy of weighing infants at 72–96 h was introduced from 1 July 2004. Two time periods were studied: pre-policy and post-policy (18 months each). Babies <28 days of age referred to hospital from the community who, on investigation, had plasma sodium concentrations of >145 mmol/l were identified. Age, plasma sodium concentration, percentage loss of body weight at presentation, breastfeeding rates at discharge and at 8 weeks, and complications due to hypernatraemia or its management were compared between the two groups. Results: 60 cases of NHD were identified: 23 before and 37 after introduction of the policy. After the policy, there was earlier recognition of NHD (median 3 vs 6 days), lower percentage weight loss (11% vs 15%), smaller increase in sodium (147 vs 150 mmol/l), and higher breastfeeding rate at discharge (73% vs 22%) and 8 weeks (57% vs 22%). All the differences were significant (p<0.01). There was one death in the pre-policy group, and none in the post-policy group. Conclusions: Weighing babies early coupled with appropriate lactation support resulted in the early recognition of NHD, with less dehydration, less severe hypernatraemia, and higher breastfeeding rates in the short and medium term.